BALIAN AS A TRADITIONAL HEALER IN BALI - K. Nastya Anggaraini, S.S., M.a. (Universitas Pendidikan Ganesha, 2025)
Bali Island is famous around the world as a tourism destination that offers natural and cultural beauty. Along with modernization, the island of Bali is also experiencing globalization which accompanies various changes. Modernization refers to changes from traditional conditions to modern social conditions. These changes occur in various sectors, from the industrial, cultural, community, and other kinds of revolutions. It can be said that there will be a possible high effect on the social, political, and economic fields as a result of these changes. Globalization can refer to the global integration of economic, political, and social characteristics culture associated with the spread of modernization across countries. David Harvey discusses globalization from the perspective of Neo-liberalism. Through globalization, the telecommunications industry will have an impact on the progress of capitalism and also expand the movement of goods and people around the world. That is where capitalism is begun to transform into Neo-liberalism. With the characteristics of the system framework Neo-liberalism, namely the existence of strong private property rights, free markets, and also trade free, Neo-liberalism gives freedom to entrepreneurship and gives freedom to every technical skill, to encourage the welfare of the community. But, there are various problems in Neo-liberalism. Although setting the financial system is very important, with deterioration individualism of business actors who are not responsible for creating speculative volatility, financial problems, or intense instability. Hence, the model Neo-liberal globalization increases social inequality in society (Harvey 2005).In addition, M. Waters (M. Waters 2001) quoted from Robertson (1991) state that Globalization concerns individuals and countries in facing influence in general and ultra-nationalistic. Therefore, globalization involves culture, social, and also phenomenological of the four elements, namely one’s self, society-national, international systems, and institutions, as well as humanity. Tourism in Bali is growing along with globalization. Tourism is in touch directly and involves the local community. Therefore, tourism affects the economy and socio-culture of the local community. Economically, tourism affects the exchange rate and the price of goods, employment opportunities, and also influence the government and the local community. Socio-cultural, with the continuous development of the industrial system, local ethnic identity, and localism exists will likely disappear. However, all cultural changes occur not solely due to tourism. The reason is that tourism is related to modern industries. The possibility of the modern industry influence is broader, and there are possibly several regions that have been influenced by modern industry before tourism developed. Besides, the impact of the influence mentioned above whether the impact is good or not depends on the social of the local community itself. In Bali, society has undergone various changes as a result of this influence. The number of immigrants who come from Indonesia who want to work in Bali is increasing, and also the number of foreigners living in Bali continues to increase. As a result, various religions and languages enter the Balinese social community, besides that, the lifestyle and cultures have changed. Apart from that, job opportunities are also increasing, the workforce in agriculture is decreasing meanwhile employment in the service sector is increasing (Nagano 2007). Although there are various changes mentioned above, traditional things such as traditional dances and ceremonies in Bali still exist until today. Of course, there are various kinds of cultures and traditions in Bali, but these things also experience changes along with changes that occur in modern society. Bali, which has experienced modernization, is changing not only in tourism which also exists in the world of medicine. The Balinese way of thinking about the treatment of diseases, the choices made regarding the means of health care are also influenced because of the current Balinese lifestyle. This research focuses on these traditions, especially in traditional medicine. More specifically, on the knowledge of medicine which is closest to the life of the Balinese people called Usada Taru Pramana. Even though the Balinese do medical treatment/care in their daily life modern Balinese people may not be aware that the knowledge they are using comes from Usada Taru Pramana. As a traditional healer, how would a Balian implements Usada Taru Pramana; knowledge; how patients who visit Balian implements traditional medicine and modern medicine. Through these cases, the present research explains modern medicine in modern Balinese society, and also understands the knowledge in terms of tourism and modernization in Bali. This knowledge will help Balinese people inside and the outsiders to re-recognize traditional Balinese culture.